Early childhood educators' teaching of digital citizenship competencies. (December 2020) - Lauricella, Alexis R.; Herdzina, Jenna; Robb, Michael
Abstract: As technology access and use increases in early childhood classrooms and at home, there is an increased need to support students' understanding of how to be safe, responsible, and cooperative digital media users. While teaching media literacy in education has some historical context, it is only relatively recently that school districts have expanded their efforts to teach other digital citizenship competencies, including internet safety, media balance, and digital footprint. The purpose of this paper is to use survey data of teachers to document how the teaching of digital citizenship competencies in elementary school varies based on factors such as demographics of the students and the amount of educator experience. Results from this descriptive study indicate that elementary educators are teaching digital citizenship as early as Kindergarten but not all competencies of digital citizenship are being taught equally. Additionally, early teaching of digital citizenship competencies is more likely to occur in suburban schools and schools with more racially-ethnically diverse students. These results have implications for education policies around supporting digital citizenship competencies starting early in formal schooling. Highlights: Nationally representative sample of K-5 teachers were surveyed. Educators are teaching digital citizen competencies as early as kindergarten. Digital citizenship skills are more likely to be taught certain types of schools. Privacy and safety and digital drama, cyberbullying, and hate speech were taught.